The Mediating Role of Brand Image on the Influence of Social Media Marketing, Consumer Online Reviews and Prices on Purchase Interest in the Millennial Generation Users of Maybelline Products in Semarang City - Putri, Martiana; Noni Setyorini; Ratih Hesty Utami Puspitasari (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The aim of this research is to determine the direct and indirect influence of social media marketing, consumer online reviews and price on purchasing interest with brand image as a mediating variable. This type of research is associative correlational, while the approach taken is quantitative. With a total of 180 female respondents from the millennial generation, Mayblline users in Semarang City. This research uses path analysis to analyze data with the help of SmartPLS SEM version 3. The results of this research prove that: (1) Social MediaMarketing has a positive and significant effect on Brand Image (2) Social Media Marketing has a positive and significant effect on Purchase Interest (3) Consumer Online Reviews have a positive and significant effect on Brand Image (4) Consumer Online Reviews do not have a positive and significant effect on Purchase Intention (5) Price has a positive and significant effect on Brand Image (6) Price has a positive and significant effect on Purchase Intention (7) Image Brand has a positive and significant effect on Purchase Interest (8) Social Media Marketing has a positive and significant influence on Purchase Interest with Brand Image as a mediating variable (9) Consumer Online Reviews has a positive and significant influence on Purchase Interest with Brand Image as a mediating variable (10) Price has a positive and significant effect on Purchase Interest with Brand Image as a mediating variable